Utility of perioperative B-type natriuretic peptide in off-pump bypass surgery - Joshi, Dikshya; Guo, Zhi Gang (Nepalese Heart Journal, 2014)
Background and Aims: This study was performed to determine clinical relevance of perioperative B-type natriuretic peptide (BNP) in patients undergoing off-pump coronary artery bypass grafting. Methods: 145 consecutive patients undergoing off-pump coronary artery bypass grafting during 8-month period were enrolled in this study. The relationship between the plasma BNP and various clinical parameters was examined. Postoperatively their main clinical endpoints including requirement of mechanical ventilator support, length of intensive care unit stay and hospital stay was closely monitored. Results: Mean preoperative BNP levels were significantly higher in patients whose left ventricular ejection fraction was less than 0.50 (P<0.00083), and New York Heart Association class (III, IV) (P<0.02). The determinants of preoperative higher level of BNP can be related to the advanced age of the patients, r=0.387 (P<0.01) and left ventricular end diastolic diameter, r=0.200 (P<0.05). Postoperative 12-hour BNP correlated significantly with the duration of mechanical ventilation, rho=0.84 (P<0.05), and postoperative hospital stay for 10 days or more, rho=0.202 (P<0.05). Logistic regression analyses showed a significant association between 12-hour BNP and the requirement of mechanical ventilation, Wald=3.956 (P<0.049, 95% CI_1.023- 20.476). Conclusion: Plasma BNP concentration is a valuable biochemical marker, is easy to measure and can effectively predict postoperative outcome in off-pump coronary artery bypass grafting. Baseline BNP had strong correlation with the age and ventricular function of the patient. Postoperatively, elevated 12-hour BNP indicated prolonged ventilation and longer duration of hospital stay. DOI: http://dx.doi.org/10.3126/njh.v11i1.10977 Nepalese Heart Journal 2014;11(1): 19-25